Using quadrupole mass spectrometry for on-line gas analysis – Gasification of biomass and refuse derived fuel. (1st January 2015) - Le, C.D.; Kolaczkowski, S.T.; McClymont, D.W.J.
Highlights: A quadrupole mass spectrometer is used to provide quantitative gas analysis data. Method is used in biomass gasification experiments in the laboratory. Experiments are performed with charcoal, wood, straw, and refuse derived fuel. Method is used on a commercial pilot-scale down-draft gasifier (using waste wood). Valuable data is gathered on H2 S and COS levels, which will help with gas clean-up. Abstract: A quantitative method of on-line gas analysis was developed, using quadrupole mass spectrometry to measure gas composition when charcoal, wood, straw, and refuse derived fuel were gasified. Despite overlapping between some of the species, the method was demonstrated on small-scale laboratory gasifiers, recording the main components (e.g. N2  ∼ 54–67 vol.%; H2  ∼ 5–13 vol.%; CO2  ∼ 15–17 vol.%; CO ∼ 10–17 vol.%), and lower levels of CH4 (∼1–2 vol.%) and O2 (∼0.1–1 vol.%) in the gas. Trace levels of H2 S (∼100–300 ppmv) and COS (∼10–30 ppmv) were also measured (important for gas clean-up strategies). On-line measurements were performed on a commercial pilot-scale down-draft gasifier (using waste wood), and the concentrations of H2 S varied from 200 to 700 ppmv, and COS from 7 to 17 ppmv. The ratio of H2 S: COS was higher than in the laboratory trials – probably because of COS hydrolysis reactions taking place in the wet scrubbing systems.